The AS NEWS DESACONTECIMENTO POSSIBILITIES OF INNOVATION FROM THE NARRATIVE OF ELIANE BRUM - Ventura, Mauro de Souza [UNESP]; Abib, Tayane Aidar [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2015)
The study presented in this paper aims to outline the basis for a news production through an interpretative analysis of the narratives of Eliane Brum. The objective is to conceptualize the jornalismo de Desacontecimentos and characterize a news practice interested in the daily lives of anonymous people. In this way, we hope to identify the differences between Brum journalism and records of the mainstream media, guided by sharing specific knowledge and a common culture between the journalistic tribe.
Keywords: JOurnalism; Journalisitic tribe; Reporting techniques; Anonymous People; Eliane Brum